MIKROEMULSIFIKASI FRAKSI TIDAK TERSABUNKAN DISTILAT ASAM LEMAK MINYAK SAWIT - Teti Estiasih; Kgs. Ahmadi; Layly Alifatur Rizqiyah (Jurnal Teknologi dan Industri Pangan, 2015)
Palm fatty acid distillate (PFAD) is a by-product of palm oil refining that contains valuable bioactive compounds such as phytosterols, tocopherol, tocotrienols, and squalene which acummulates in unsa-ponifiable fraction (USF). In the form of emulsion, USF will be convenient and easy to use as food supplements or fortificants. Microemulsion is a type of emulsion that has stable droplet sizes less than 10 mm. Hence, the best emulsifier for USF microemulsion is important to be determined. The USF micro-emulsion was prepared by homogenizing the sample mixtures at 12.000 rpm for 20 min at USF concentration of 10% (w/v) with lecithin and tween 80 as emulsifiers at concentration of 0.5,1.0, and 1.5% (w/v). The microemulsions were analyzed for their viscosity, stability, and particle size distributions, as well as microstructures. The results showed that characteristics of microemulsion were affected by emulsifier types and concentrations. Tween 80 produced better microemulsion than lecithin indicated by more stable emulsions, smaller droplet sizes, and narrower ranges of droplet size distributions. The increasing lectihin concentrations resulted in a narrower droplet size distribution but the average droplet size was not always smaller. Conversely, the increasing tween 80 concentrations increased average droplet sizes and ranges of particle size distributions. The most suitable emulsifier for USF microemulsion was tween 80 at concen-tration of 0.5%. This microemulsion contained bioactive compounds derived from USF, namely vitamin E (mainly tocotrienols), phytosterols, and squalene.